Trade Consequences of the Farm Production Regulation: The Glyphosate Ban in the Sri Lankan Tea Industry - Rathnayake, Chinthani; Malcolm, Bill; Griffith, Garry; Sinnette, Alex (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2022)
Abstract Tea manufacturing is an important industry for the Sri Lankan economy because it generates foreign income, which adds to gross domestic product of the country and creates employment opportunities. Tea has been exported to several countries from Sri Lanka for over a century, and Sri Lanka remains a leading tea exporter to date. Recently, the Sri Lankan government issues a policy which disadvantages the tea industry in the country. The government banned the use of glyphosate in the agricultural sector from 2015 to 2018 which directly or indirectly affects the tea industry. The policy brought a consequence where the farmers used illegal substances and other weedicides to control the weed. These consequences placed the Sri Lankan tea industry at risk since their final product is contains high amount of residual weedicide which exceeds the Maximum Residue Limit (MRL). In this paper, we use The Equilibrium Displacement Model to study the economic impact of rejections of tea consignments by Japan due to the excess use of 2-methyl-4-chlorophenoxyacetic acid (MCPA) in 2018. The demand of Sri Lankan bulk black tea by Japan has declined by 6.5% between 2017 and 2018. The estimated of the Sri Lankan tea industry from reduced demand for bulk black tea was Rs339 million.Keywords: tea industry, glyphosate ban, Sri Lanka AbstrakTeh adalah industri penting bagi perekonomian Sri Lanka karena menghasilkan devisa yang menambah produksi domestik bruto dan menciptakan lapangan kerja. Teh telah diekspor dari Sri Lanka selama lebih dari satu abad ke berbagai negara dan Sri Lanka tetap menjadi eksportir utama. Kebijakan pemerintah baru-baru ini yang memengaruhi sektor pertanian tidak menguntungkan bagi industri teh. Pelarangan penggunaan glifosat dari tahun 2015 hingga 2018 merupakan salah satu kebijakan yang berdampak signifikan terhadap industri teh, baik secara langsung maupun tidak langsung. Konsekuensi penggunaan formulasi pengendali gulma ilegal dan herbisida alternatif menempatkan industri teh pada keadaan yang beresiko melalui konsekuensi tidak disengaja dari kehilangan akses ke pasar ekspor teh karena insiden mengenai kelebihan Batas Maksimum Residu. Dalam tulisan ini, dampak ekonomi dari penolakan pengiriman teh dari Jepang karena penggunaan 2-methyl-4-chlorophenoxyacetic acid (MCPA) yang berlebihan pada tahun 2018 diselidiki dengan menggunakan Equilibrium Displacement Model pada industri teh. Permintaan ekspor Jepang untuk teh hitam curah turun 6,5% antara 2017 dan 2018. Perkiraan kerugian surplus ekonomi industri teh Sri Lanka dari penurunan permintaan teh hitam curah adalah Rs339 juta.Kata kunci: industri teh, larangan penggunaan glifosat, Sri Lanka